Rabbi Paul an intellectual biography - Chilton, Bruce (Doubleday, 2004)
A portrait of Saint Paul identifies his crucial role in the formation of Christianity while considering how beliefs about his character have transformed him from a premiere apostle into a doctrine-promoting antifeminist and homophobe.